Consilience: The unity of knowledge - Wilson, Edward O. (London Abacus, 1998)
"A dazzling journey across the sciences and humanities in search of deep laws to unite them." --The Wall Street Journal One of our greatest living scientists--and the winner of two Pulitzer Prizes for On Human Nature and The Ants--gives us a work of visionary importance that may be the crowning achievement of his career. In Consilience (a word that originally meant "jumping together"), Edward O. Wilson renews the Enlightenment's search for a unified theory of knowledge in disciplines that range from physics to biology, the social sciences and the humanities.Using the natural sciences as his model, Wilson forges dramatic links between fields. He explores the chemistry of the mind and the genetic bases of culture. He postulates the biological principles underlying works of art from cave-drawings to Lolita. Presenting the latest findings in prose of wonderful clarity and oratorical eloquence, and synthesizing it into a dazzling whole, Consilience is science in the path-clearing traditions of Newton, Einstein, and Richard Feynman.Editorial ReviewsAmazon.com ReviewThe biologist Edward O. Wilson is a rare scientist: having over a long career made signal contributions to population genetics, evolutionary biology, entomology, and ethology, he has also steeped himself in philosophy, the humanities, and the social sciences. The result of his lifelong, wide-ranging investigations is Consilience (the word means "a jumping together," in this case of the many branches of human knowledge), a wonderfully broad study that encourages scholars to bridge the many gaps that yawn between and within the cultures of science and the arts. No such gaps should exist, Wilson maintains, for the sciences, humanities, and arts have a common goal: to give understanding a purpose, to lend to us all "a conviction, far deeper than a mere working proposition, that the world is orderly and can be explained by a small number of natural laws." In making his synthetic argument, Wilson examines the ways (rightly and wrongly) in which science is done, puzzles over the postmodernist debates now sweeping academia, and proposes thought-provoking ideas about religion and human nature. He turns to the great evolutionary biologists and the scholars of the Enlightenment for case studies of science properly conducted, considers the life cycles of ants and mountain lions, and presses, again and again, for rigor and vigor to be brought to bear on our search for meaning. The time is right, he suggests, for us to understand more fully that quest for knowledge, for "Homo sapiens, the first truly free species, is about to decommission natural selection, the force that made us.... Soon we must look deep within ourselves and decide what we wish to become." Wilson's wisdom, eloquently expressed in the pages of this grand and lively summing-up, will be of much help in that search. --This text refers to an out of print or unavailable edition of this title.From Library JournalHistorically, all of the sciences were once united under the rubric of "natural science." Over time, they became fragmented and specialized. Nevertheless, Wilson argues that there is a genetic and neurological basis for knowledge and that all subjects of human inquiry can be reunited under the umbrella of "consilience." Copyright 1999 Reed Business Information, Inc. --This text refers to an out of print or unavailable edition of this title.